Colagem, antropofagia e subversão em Galvez imperador do Acre, de Márcio Souza - SANTOS, Francisco Ewerton Almeida dos (Universidade Federal do Pará, 2012)
This paper discusses the novel Galvez imperador do Acre, Amazon published in 1976 by the Amazonas’s writer Márcio Souza, establishing relationships between the literary and the aesthetic avant-garde modernist proposals, both in Europe and Brazil, offering thus the investigation of the relationship between modernism and Post-Modernism, and the relations between literature, society, history and culture. We will address issues such as the redefinition of literary texts or not in Galvez imperador do Acre through the process of collage and intertextuality, the relationship between the novel and the historical moment which incorporates, as well as one in which it was produced, the rescue of the past a critical and transformative approaches and possibilities of reading the literary text with a view to theories post-modernist and post-colonialists. We observe, therefore, how it reproduces the Belle Epoque and the extraction of latex in the Amazon and its aesthetic fragmentary, consisting of several citations of canonical authors, investigating the functioning of collage and cannibalism as the main tools of subversion to the complaint and cultural process Import of European values lived by Amazon capitals at the time represented by the novel and whose criticism can be extrapolated to the whole process of cultural formation in Brazil and the Amazon. For this, we will bring into question the theories of Jacques Derrida, Walter Benjamin, Claude Levi-Strauss, Fredric Jameson, Luiz Costa Lima, Antonio Candido, Aijaz Ahmad, Homi Bhabha, Stuart Hall, Canclini, Silviano Santiago, Angel Rama, Linda Hutcheon, Antoine Compagnon, among others, in order to, from the novel under review, deepen the theoretical discussion about the relationship between literary texts and comparative between Literary Studies and other fields of study.